Strategy in Asia the past, present, and future of regional security - Mahnken, Thomas G.; Blumenthal, Dan (Stanford University Press, 2014)
Some of the United States' greatest challenges over the coming decades are likely to emanate from the Asia-Pacific region. China and India are rising and Militant Islam continues to take root in Pakistan, while nuclear proliferation threatens to continue in fits and starts. If America is to meet these challenges comprehensively, strategists will have to learn more about Asia, and Asian scholars, policymakers, and analysts will need to understand better the enduring and timeless principles of strategy.